Electrochemical Polymerization and Biological Activity of 4-(Nicotinamido)-4-Oxo-2-Butenoic Acid as An Anticorrosion Coating on A 316L Stainless Steel Surface - Sana A. Habeeb; Khulood A. Saleh (Iraqi Journal of Science, 2021)
In this study, poly4-(nicotinamido)-4-oxo-2-butenoic acid (PNOE) was prepared by the electro polymerization of 4-(nicotinamido)-4-oxo-2-butenoic acid (NOE) monomer on a 316 stainless steel (St.St) which acts as an anticorrosion coating. Fourier transforms infrared (FTIR), atomic force microscopy (AFM), scanning electron microscopy (SEM), and cyclic voltammetry were used to diagnose the structure and the properties of the prepared polymer layer. The corrosion behavior of the uncoated and coated 316 St.St were evaluated by using an electro chemical polarization technique in 0.2 M hydrochloric acid solution as a corrosive medium at a temperature range of 293 to 323 K. Nano materials, such as nano ZnO and graphene were added in different concentrations to the monomer solution for improving the corrosion resistance of the 316 St.St surface. The results showed that the values of protection efficiencies of the polymeric coating were increased after adding the nano materials. The kinetic and thermodynamic activation parameters were also calculated and the biological activity of the polymer film against Gram negative and positive bacteria was studied.